2019
DOI: 10.1111/1440-1681.13074
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol protects against hepatic insulin resistance in a rat's model of non‐alcoholic fatty liver disease by down‐regulation of GPAT‐1 and DGAT2 expression and inhibition of PKC membranous translocation

Abstract: Summary Non‐alcoholic fatty liver disease (NAFLD) is associated with hepatic insulin resistance (IR). Resveratrol (RES) a potent hypolipidemic dietary polyphenol has been identified for its ability to prevent hepatic steatosis and hepatic IR in high‐fat diet (HFD)‐fed murine models of NAFLD. In the present study, we have carried an in vivo animal experiment to identify a novel mechanism for RES protective action. Sub‐chronic (45 days) RES pretreatment in 3 days HFD‐fed adult Wistar rats prevented early hepatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…HFD feeding for six weeks induced a significant increase of both body weight gain, in accordance to juvenile obesity development, and biochemical parameters such as ALT and LDL, suggesting altogether an induced metabolic alteration in concordance with our previous results [ 24 ]. Besides, HFD diet group presented a remarkable increase in plasma insulin concentration and HOMA-IR index, which is closely linked to hepatic insulin resistance in NAFLD [ 37 ]. Additionally, HFD feeding also induced a gut microbiota imbalance at all taxonomic levels.…”
Section: Discussionmentioning
confidence: 99%
“…HFD feeding for six weeks induced a significant increase of both body weight gain, in accordance to juvenile obesity development, and biochemical parameters such as ALT and LDL, suggesting altogether an induced metabolic alteration in concordance with our previous results [ 24 ]. Besides, HFD diet group presented a remarkable increase in plasma insulin concentration and HOMA-IR index, which is closely linked to hepatic insulin resistance in NAFLD [ 37 ]. Additionally, HFD feeding also induced a gut microbiota imbalance at all taxonomic levels.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has demonstrated that hepatic insulin resistance is the primary event in free fatty acid–induced whole-body insulin resistance. And muscle and adipose tissue insulin resistance may be the consequence of hepatic insulin resistance (Perry et al, 2014; Badi et al, 2019; Medak and Townsend, 2019). Recent evidence has shown that muscle- and adipose tissue–specific IR knockout mice only show muscle or adipose tissue insulin resistance, but total body glucose metabolism still remains normal (Perseghin, 2009).…”
Section: The Liver Is the First Organ To Develop Insulin Resistancementioning
confidence: 99%
“…However, subsequent gene deletion studies have shown that the formation of MPTP does not require ANT and VDAC, partly due to the presence of different subtypes of these putative pore components. Despite these observations, it is generally believed that Cyp-D is the main factor in the formation of MPTP (Zhou et al, 2019;Badi et al, 2019;Medak & Townsend, 2019).…”
Section: Discussionmentioning
confidence: 99%